EFFECT OF IRON AND ZINC FORTIFICATION ON CHEMICAL COMPOSITION OF WHOLE WHEAT FLOUR - Akhtar, Saeed; Anjum, Faqir M.; Saleem-ur-Rehman, (Journal of Research (Science), 2005)
Whole wheat flour fortified with different zinc and iron salts at various dose level, packed in polypropylene bags and tin boxes, stored under two different conditions for a period of sixty days was tested periodically for changes in moisture, ash, protein and fat content. Storage conditions, storage periods and treatments significantly affected moisture content of flour samples. Packaging material had no effect on the moisture content of whole wheat flour during the entire storage period. Treatment effect was found to be significant for ash content in flour samples. Statistical results indicated that storage conditions and storage periods significantly affected fat content of fortified and unfortified flour samples. The fat content was found to be significantly higher in whole wheat flour samplesstored at ambient storage conditions than flour samples stored under controlled conditions. The fat content decreased significantly as a function of storage period irrespective of storage conditions. The fortification, storage conditions and packaging materials exerted non significant effect on protein content of flour samples while a significant change in protein content was observed as function of the storage period. The protein content decreased over the entire storage period.